2014
DOI: 10.1371/journal.pgen.1004089
|View full text |Cite|
|
Sign up to set email alerts
|

ABCC5, a Gene That Influences the Anterior Chamber Depth, Is Associated with Primary Angle Closure Glaucoma

Abstract: Anterior chamber depth (ACD) is a key anatomical risk factor for primary angle closure glaucoma (PACG). We conducted a genome-wide association study (GWAS) on ACD to discover novel genes for PACG on a total of 5,308 population-based individuals of Asian descent. Genome-wide significant association was observed at a sequence variant within ABCC5 (rs1401999; per-allele effect size = −0.045 mm, P = 8.17×10−9). This locus was associated with an increase in risk of PACG in a separate case-control study of 4,276 PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 43 publications
0
45
0
4
Order By: Relevance
“…48–50 That anterior chamber depth is affected by race and ethnicity as well as age and gender suggests a potential role for genetic influences, which is consistent with a recent report of a genetic variant within the ABCC5 gene that influences anterior chamber depth and the risk of PACG among Asians. 51 The possibility that the risk of certain subtypes of glaucoma could be mediated by the genetic variants linked to refractive errors or the susceptibility to the same warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…48–50 That anterior chamber depth is affected by race and ethnicity as well as age and gender suggests a potential role for genetic influences, which is consistent with a recent report of a genetic variant within the ABCC5 gene that influences anterior chamber depth and the risk of PACG among Asians. 51 The possibility that the risk of certain subtypes of glaucoma could be mediated by the genetic variants linked to refractive errors or the susceptibility to the same warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent GWA study of ACD and PACG in an Asian cohort, variants in the ATP-binding cassette, sub-family C (CFTR/MRP), and member 5 encoding gene (ABCC5) were found to influence ACD and increase the risk of PACG development. 94 ABCC5 has been shown to participate in tissue defense and cellular signal transduction mechanisms. 95 The findings of this study support the role of ACD-modifying variants in mediating risk to PACG.…”
Section: Nebmentioning
confidence: 99%
“…Another GWAS confirmed the association at these three loci and found significant association of five additional loci with PACG [13]. Nongpiur et al conducted a two-staged GWAS and found that a genetic variant within ABCC5 gene may increase the risk of having PACG by shaping the anterior chamber depth (ACD) [14]. …”
Section: Introductionmentioning
confidence: 99%